The Role of Light–Dark Regulation of the Chloroplast ATP Synthase - Kohzuma, Kaori; Froehlich, John E.; Davis, Geoffry A.; Temple, Joshua A.; Minhas, Deepika; Dhingra, Amit; Cruz, Jeffrey A.; Kramer, David M. (Frontiers in Plant Science, 2017)
The chloroplast ATP synthase catalyzes the light-driven synthesis of ATP and is activated in the light and inactivated in the dark by redox-modulation through the thioredoxin system. It has been proposed that this down-regulation is important for preventing wasteful hydrolysis of ATP in the dark. To test this proposal, we compared the effects of extended dark exposure in Arabidopsis lines expressing the wild-type and mutant forms of ATP synthase that are redox regulated or constitutively active. In contrast to the predictions of the model, we observed that plants with wild-type redox regulation lost photosynthetic capacity rapidly in darkness, whereas those expressing redox-insensitive form were far more stable. To explain these results, we propose that in wild-type plants, down-regulation of ATP synthase inhibits ATP hydrolysis, leading to dissipation of thylakoid proton motive force (pmf) and subsequent inhibition of protein transport across the thylakoid through the twin arginine transporter (Tat)-dependent and Sec-dependent import pathways, resulting in the selective loss of specific protein complexes. By contrast, in mutants with a redox-insensitive ATP synthase, pmf is maintained by ATP hydrolysis, thus allowing protein transport to maintain photosynthetic activities for extended periods in the dark. Hence, a basal level of Tat-dependent, as well as, Sec-dependent import activity, in the dark helps replenishes certain components of the photosynthetic complexes and thereby aids in maintaining overall complex activity. However, the influence of a dark pmf on thylakoid protein import, by itself, could not explain all the effects we observed in this study. For example, we also observed in wild type plants a large transient buildup of thylakoid pmf and nonphotochemical exciton quenching upon sudden illumination of dark adapted plants. Therefore, we conclude that down-regulation of the ATP synthase is probably not related to preventing loss of ATP per se. Instead, ATP synthase redox regulation may be impacting a number of cellular processes such as 1) the accumulation of chloroplast proteins and/or ions or 2) the responses of photosynthesis to rapid changes in light intensity. A model highlighting the complex interplay between ATP synthase regulation and pmf in maintaining various chloroplast functions in the dark is presented.